Ethnobotanical Uses and Antimicrobial Properties of Plants in Small‐Scale Tropical Fish Farms: The Case of Indonesian Fish Farmers in Java (Indonesia). Issue 1 (4th August 2016) - Caruso, Domenico; Lusiastuti, Angela Maria; Taukhid, Taukhid; Avarre, Jean‐Christophe; Yuhana, Munti; Sarter, Samira
Abstract: Among the most common plants used by fish farmers in Java, 18 were selected for deeper ethnobotanical and laboratory investigation into their antimicrobial activity. These plants are mainly used against fish diseases, but with no precise therapeutic indication, leading to low specificity of use. Leaves, which were the most commonly used part of plants, were generally placed directly in water or less frequently added to the feed. Disk diffusion tests showed that 15 plants of the 18 (83%) displayed varying degrees of antibacterial activity and that Streptococcus agalactiae was more sensitive than Aeromonas hydrophila . Crude ethanolic extracts (EE) were more active than water macerates (WM), and minimum inhibitory concentrations (MICs) ranged from 12.5 to 25 mg/mL. Only the EE of Piper betle had an inhibitory effect against A. hydrophila . No MIC was found for any of the WM studied here. Furthermore, both the EE and, to a lesser extent, the WM of active plants were able to reduce bacterial growth by more than 99%, even at doses below their MICs. These results suggest that these plant extracts have a potential for eco‐friendly prevention of bacterial fish diseases.